Pengaruh Kecerdasan Intelektual dan Kecerdasan Spiritual terhadap Kinerja Karyawan : Studi Kasus pada Pekerja Non Manajer pada Hotel Laut Biru Pangandaran - Rifa Melinda Nurachman; Arga Sutrisna; Barin Barlian (CV. Ulil Albab Corp, 2022)
This study aims to determine and analyze the influence of intellectual intelligence and spiritual intelligence on employee performance (a case study on non-manager workers at Laut Biru Pangandaran Hotel). The method used in this research is causality through a case study approach. With a research sample of 51 non- manager workers at the Laut Biru Pangandaran Hotel. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that simultaneously intellectual intelligence and spiritual intelligence had a significant effect on employee performance. Partially Intellectual Intelligence has a significant influence on Employee Performance. In contrast to Spiritual Intelligence does not have a significant effect on employee performance.